Impaired neural habituation to neutral faces in families genetically enriched for social anxiety disorder. Issue 12 (10th October 2019) - Bas‐Hoogendam, Janna M.; van Steenbergen, Henk; Blackford, Jennifer Urbano; Tissier, Renaud L. M.; van der Wee, Nic J. A.; Westenberg, P. Michiel
Abstract: Background: Social anxiety disorder (SAD) is an incapacitating disorder running in families. Previous work associated social fearfulness with a failure to habituate, but the habituation response to neutral faces has, as of yet, not been investigated in patients with SAD and their family members concurrently. Here, we examined whether impaired habituation to neutral faces is a putative neurobiological endophenotype of SAD by using data from the multiplex and multigenerational Leiden Family Lab study on SAD. Methods: Participants ( n  = 110; age, 9.2 – 61.5 years) performed a habituation paradigm involving neutral faces, as these are strong social stimuli with an ambiguous meaning. We used functional magnetic resonance imaging data to investigate whether brain activation related to habituation was associated with the level of social anxiety within the families. Furthermore, the heritability of the neural habituation response was estimated. Results: Our data revealed a relationship between impaired habituation to neutral faces and social anxiety in the right hippocampus and right amygdala. In addition, our data indicated that this habituation response displayed moderate ‐ to‐moderately high heritability in the right hippocampus. Conclusion: The present results provide support for altered habituation as a candidate SAD endophenotype; impaired neural habitation cosegregrated with the disorder within families and was heritable. These findings shed light on the genetic susceptibility to SAD.